NOx precursors from biomass pyrolysis: Distribution of amino acids in biomass and Tar-N during devolatilization using model compounds. (1st January 2017) - Chen, Hanping; Si, Yaohui; Chen, Yingquan; Yang, Haiping; Chen, Deming; Chen, Wei
Highlights: 60–80% of nitrogen in biomass is existed as protein-N. 9 types of amino acids are recommended to be used as model amino acids. Cellulose promotes higher N-containing chemical selection at higher heating rate. Amino acids can effect N distribution and N-containing chemicals formation. Glutamic acid and alanine can promote more heterocyclic form. Abstract: To elucidate the mechanism of nitrogen transformation during biomass combustion, the formation behavior of NOx precursors during biomass devolatilization was investigated using two types of pyrolysis reactors at different heating rates (13 °C/s and 10 4 °C/s) with model compounds (i.e., mixtures of various amino acids and cellulose/lignin). It was found that 60–80% nitrogen existed as protein-N. Cellulose promoted the formation of a greater amount of N-containing compounds at higher heating rates but resulted in the conversion of nitrogen into tar with a smaller amount of N-containing compounds at lower heating rates. Lignin promoted the transformation of nitrogen into gaseous products at lower heating rates. Higher heating rates were found to disfavor the interaction between the amino acids and lignin. However, different amino acids had different effects on the nitrogen transformation in biomass. Glutamic acid resulted in the lowest nitrogen distribution in gas and the highest distribution in tar, phenylalanine caused the conversion of a large amount of nitrogen into gaseous products, while the resulting char captured the lowest amount of nitrogen. Glutamic acid and alanine promoted the formation of N-containing heterocyclic compounds, while copyrolysis with phenylalanine afforded N-containing compounds with NH2 and CN groups.